Texts and contexts of the Book of Sirach = Texte und Kontexte des Sirachbuches - Karner, Gerhard; Ueberschaer, Frank; Zapff, Burkard M. (Septuagint and cognate studies, 2017)
Key aspects and themes in recent scholarship on the Book of Ben Sira / Markus Witte -- Der soziokulturelle Hintergrund des Sirachbuches / Siegfried Kreuzer -- Jesus Sirach: Ein Jüdischer Weisheitslehrer in hellenistischer Zeit / Otto Kaiser -- Die Konstruktion von Kultur im Sirachbuch / Oda Wischmeyer -- Scribal practices in the Ben Sira Hebrew Manuscript A and codicological remarks / Jean-Sébastien Rey -- The literary and linguistic subtlety of the Greek version of Sirach / James K. Aitken -- Das Griechisch des Jesus Sirach / Knut Usener -- Sirach 10:1-18: Some observations on the work of the translator / Benjamin G. Wright -- Language and textual history of Syriac Ben Sira / Jan Joosten -- Die Vorlage der syrischen Sirachübersetzung und die gereimte hebräische Paraphrase zu Ben Sira aus der Ben-Ezra-Geniza / Franz Böhmisch -- Einige hermeneutische Boebachtungen zur syrischen Version des Sirach / Burkard M. Zapff -- Der lateinische text des Ecclesiasticus: Von Philipp Thielmann bis zu Walter Thiele / Pierre-Maurice Bogaert -- Plerique codices, nonnulli codices: Ambrose's Biblical Text: the case of Ben Sirach and the Canticum Canticorum / Anthony J. Forte -- Sir 51,1-12: Anhang oder Knotenpunkt? / Werner Urbanz